De-repression of CTGF via the miR-17-92 cluster upon differentiation of human glioblastoma spheroid cultures - Ernst, Aurélie; Campos, Benito; Meier, Jan; Devens, Frauke; Liesenberg, F.; Wolter, M.; Reifenberger, G.; Herold-Mende, Christel; Lichter, Peter; Radlwimmer, Bernhard (Oncogene, 2010)
All-trans retinoic acid is a potent promoter of cellular differentiation processes, which is used in cancer therapy. Glioblastoma spheroid cultures are enriched in tumor-initiating cells, and provide a model to test new treatment options in vitro. We investigated the molecular mechanisms of response to exposure to differentiation-promoting conditions in such cultures. Microarray analyses of five independent cultures showed that after induction of differentiation, inhibitors of transforming growth factor-β/bone morphogenetic protein, Wnt/β-catenin and IGF signaling were upregulated, whereas expression of several microRNAs decreased, particularly that of the miR-17-92 cluster. In primary astrocytic gliomas (n=82), expression of several members of miR-17-92 was significantly higher relative to those of normal brain (n=8) and significantly increased with tumor grade progression (P<0.05). A high-level amplification of the miR-17-92 locus was detected in one glioblastoma specimen. Transfection of inhibitors of miR-17-92 induced increased apoptosis and decreased cell proliferation in glioblastoma spheroids. Mir-17-92 inhibition was also associated with increased messenger RNA (mRNA) and/or protein expression of CDKN1A, E2F1, PTEN and CTGF. The CTGF gene was shown to be a target of miR-17-92 in glioblastoma spheroids by luciferase reporter assays. Our results suggest that miR-17-92 and its target CTGF mediate effects of differentiation-promoting treatment on glioblastoma cells through multiple regulatory pathways.